Perancangan Sistem Informasi Persetujuan Online Pemilihan Vendor Supplier dengan Framework Django (Kasus PT Astra Komponen Indonesia) - Haryo Mukti Wibowo; Melkior Nikolar Ngalumsine Sitokdana (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
The Vendor Selection Process is a procedure in which a company compares materials from several vendor suppliers and determines which vendor has the best score and is most suitable to be selected and partnered with for the procurement of production materials. PT Astra Komponen Indonesia has encountered several issues within this vendor selection process, including inefficiency due to the high manpower requirement and several obstacles that hinder timely approvals among parties involved. Therefore, an online vendor selection approval system is needed. This research adopts the Waterfall development method. The system is designed and implemented as a web-based application using the Django framework, which is based on the Python programming language, and utilizes PostgreSQL as its database system. The results of this research and system development have significantly improved the material procurement process in the company, particularly in terms of workforce efficiency, time savings, equipment asset usage, and minimizing approval process delays.